Perlindungan Hukum Atas Pengiriman Barang Dari Luar Negeri Dengan Menggunakan Angkutan Udara (Studi pada Kantor Cabang Delivery Hotline Losing/DHL Surakarta ) - Wisdarisman, Ragil, Shlalman Al-Farizy, SH. M.Kn (2016)
The purpose of this study was to describe the procedure and the implementation of the delivery of goods from overseas to Indonesia, the problems that arise and the settlement of problems in the implementation of the delivery of goods from overseas to Indonesia via DHL. This research includes juridical empirical legal research (sociological) using primary data as basic data. Data were analyzed using qualitative analysis. The results showed that: First, the provisions of the delivery of goods from overseas to Indonesia via air freight at DHL is included import procedures called DHL Import Express Worldwide. The provisions that have been standardized in the proof of delivery or receipt received packages (Way Bill) as well as the points of the agreement. Terms and conditions or rules applicable to shipping via DHL package are: the provisions regarding customs, exports and imports; provisions regarding submissions can not be accepted; provisions regarding delivery can and can not do; provisions on inspections; provisions on shipping costs; provisions concerning the responsibility of DHL; provisions regarding the time limit for submission of claims; provisions on insurance items; provisions regarding pending items and money back guarantee; provisions on circumstances beyond the control of DHL; provisions regarding international conventions; provisions on warranties and indemnities by the sender; provisions regarding the determination of these; provisions on governing law; and the provision of separation packages; Second, in the event of dispute resolution in the process of transportation. The carrier is obliged to complete the document on the goods which he sent in the mail charge air, are obliged to store these items in the right place at the expense of the consignee and immediately notify the consignee that the goods have arrived. The carrier is obliged to be responsible for replacing losses that arise in the implementation of the transport to the sender, but not all the losses appear to be the responsibility of the carrier to replace them because the carrier is not liable for damages caused by: Circumstances force (coercion or force majeure), defects in the goods themselves, errors or omissions of the shipper, the delay in the arrival of goods at the destination due to force majeure, in which case the goods are not damaged or destroyed.